Environmental Pollution Prevention Effort Soun Noodle Industry Waste in Two (2) Village, Tulung District, Klaten Regency - Imam Wisnu Kurniyanto; Ipmawan Muhammad Iqbal; Farhan Rizky Darmawan; Muhammad Faizal Rifai; Nugroho Budi Kisdiyanto (Universitas Muhammadiyah Surakarta, 2022)
Pucang Miliran Village and Daleman Village are the largest buckwheat noodle industry/SME centers in Tulung District, Klaten Regency, Central Java.Pollution is not only caused by large and medium scale industries, but can also be caused by small scale industries, one of which is the vermicelli noodle industry which also produces liquid waste and solid waste. The problems in this study are how to prevent environmental pollution due to the production of home-based